Status Infeksi Torque Teno Virus (TTV) Komunitas Gigolo Surakarta - Engine Rabindra Ariapramuda; Afiono Agung Prasetyo; Hudiyono Hudiyono (Nexus Biomedika, 2014)
Background: Torque Teno Virus ( TTV ) is the first circular single-stranded DNA virus that is reported to infect humans. TTV infection has been implicated in the development of various diseases . However, it is still unclear how the mechanisms of TTV in the pathogenesis of various diseases. TTV infection was found not only in people with illness, but also found in general population with good health. Methods: There were 30 male sex workers (MSW) in Surakarta, which were included as our respondents. We took respondences bloos and isolated its DNA, in addition respondents underwent to face-to-face interview and filled questionnaire. Then, we ran polymerase chain reaction (PCR) nested with primer (NG059/NG063 and NG061/NG063) to detect N22 sequence of TTV. We ran electrophoresis in 2% agarose gel with Loading Quick ?X174/HaeIII 72-1353bp as a marker. Then, we visualized the gel on Gel Documentation and interpretated. Data of TTV infection, respondents description, risk factors of TTV, and results of HIV and HCV infection from previous study were analyzed using Chi Square. Results: About 7 (7/30, 23.3%) respondents were infected by TTV. There was any correlation (p < 0.050) between TTV infection and having piercing (p = 0.029). However, there was no correlation (p > 0.050) between TTV infection and performed unprotected vaginal sex (p = 0.481), unprotected anal sex (p = 0.269), injecting drug users (p = 0.065), and having a tattoo (p = 0.925). Respondents having piercing (Odds ratio [OR] = 7.083; 95% Confidence Interval [CI] : 1.075 46.678) and performed unprotected vaginal sex (OR = 1.923; 95% CI : 0.307 12.053) were more likely to be infected with TTV. About 2 (2/3, 66.7%) respondents who infected with HIV and 2 (2/7, 28.6%) respondents who infected with HCV were also infected with TTV. Respondents who infected by HIV (OR = 8.800; 95% CI : 0.661 117.234) and HCV (OR = 1.440; 95% CI : 0.212 9.782) were more likely to be infected with TTV. Conclusion: Prevalence of TTV infection among MSW in Surakarta is lower than other community in Indonesia. Further research is needed to determine status of TTV infection among MSW community and other high-risk community, and to find out the certain risk factors of TTV infection. Keywords: TTV, Male Sex Workers (MSW), Surakarta